Divided Digitally: Literacy in the 21st Century - Wilson, Olivia; Stockman, John Cameron; Nickerson, Tyler; Annear, Tim (My University, 2013)
Socioeconomic inequalities receive much attention in academic literature, but scholars are just beginning to grasp what may amount to one of the most significant disparities of the 21st century: that of technological literacy. As technological skill becomes an increasingly crucial element of everyday life -- especially regarding educational and career opportunities -- it is becoming apparent that more research is needed on the 'digital divide.' Although information and communications technologies are penetrating deeper into society, there remain critical differences in how individuals access, navigate, and benefit from these advancements. Here, we will conceptualize the key concepts of the digital divide and technological literacy and evaluate policy measures designed to combat the digital divide. Then, we analyze results from a survey designed to gauge technological literacy in Madison, Wisconsin to help determine if there exists gaps in technological literacy, and what sort of demographic and socioeconomic factors are linked to such gaps. Additionally, since public schools are a "critical domain within which the digital divide is manifested, reproduced, and sometimes overcome," we examine disparities in how technology is being taught in primary and secondary schools across Wisconsin. This socio spatial analysis has provided what we believe is substantial evidence of a divide in digital literacy across socioeconomic lines and striking disparities in how technology skills are being taught in public schools. However, given limitations in our ability to collect adequate data on some aspects of the divide and the prescient nature of this understudied field, we recommend future research to fully grasp the scope and impact these forces may have.
Includes Figures, Maps, Illustrations and Bibliography.
Keywords: Madison; Technological Literacy; Digital Divide